Urgensi Bahan Ajar Interakitf Berbasis Information and Communication Technologies (ICT) dalam Pembelajaran Menulis - Prasetyo Yuli Kurniawan; Subyantoro Subyantoro; Rahayu Pristiwati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Post-pandemic changes behavior and actions in all fields, especially the field of education. The digitization of education at this time is something that must be mastered by teachers. If teachers do not master Information and Communication Technologies (ICT), it will be outdated. The learning that is currently carried out must be integrated into technology. One that can be used is ICT-based interactive teaching materials even though there are still problems in writing learning. Writing learning on an independent curriculum must contain a learner profile. This research reviews the importance of ICT-based interactive teaching materials in writing learning. The results of the analysis of several articles show that ICT-based interactive teaching materials are one way to implement learning today. In addition, interactive teaching materials need to be loaded with Pancasila student profiles in accordance with the Kurikulum Merdeka.